Awal Mula dan Rutinitas Bersepeda Tidak Mempengaruhi Indeks Massa Tubuh (IMT) - Muhammad Fadhol Romdhoni, M.Si.; Yuhantoro Budi Handoyo Sakti; Dewi Karita (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2019)
Research in Semarang 9.1% and 10.6% of children aged 6-7 years, suffered from overweight and obesity, with the ratio of boys are higher than girls. Lifestyle changes is the first step to regulate body mass index back to normal. Healthy active lifestyle is now being campaigned, one of exercises that recently famous is biking. This research is to find out the relationship between time baseline with IMT and biking routine with IMT. This study is a one group survey without a control design. The method used in this study is a cross sectional survey. Respondents are biker who agreed to participated in this study. This study was conducted of 173 respondents. Non-parametric statistical analysis test using Kolmogorov smirnov (alternative test of chi square reasons the data does not meet the requirements). Data on the relationship between time baseline and BMI was p = 0.654 (p> 0.05), shows that time baseline is not related with body mass index (BMI) values. Furthermore, the relationship of biking routines with BMI was p = 0.376 (p> 0.05), which is not related between biking routines and body mass index (BMI) values. In conclusion, that time baseline and biking routines have no relationship to the body mass index value, as one of obesity indicator.